Business and community in Medieval England : the Cambridge Hundred Rolls Sources volume - Casson, Catherine; Casson, Mark; Lee, John S.; Phillips, Katie (Bristol University Press, 2020)
One of the most important manuscripts survived from the thirteenth-century England, the documents known as the Hundred Rolls for Cambridge have been incomplete until the recent discovery of an additional roll. Offering new translations and additional appendixes, this invaluable volume updates the inaccurate transcription of 1818.